Necesidad de establecer en la ley de jurisidiccion contencioso administrativa los requisitos fundamentales y la forma adecuada de procedibilidad, en la accion de lesividad - Diaz Solis, Karol Dayana (2015)
The general interest in administered at a given time , may require an administrative act is withdrawn from the legal world, become inconvenient ; however, the administration for reasons of legal certainty, or because the law does not empower it , or because the law does not clearly state that you can remove that legal act; the same can not be removed However, if the interest is demanding the termination of an act , which at first was for the common good or contrary to it, should be removed . The administration can not sit idly ; must give a solution , that solution is in the detrimental action as a means through which could be removed from the legal life an act allegedly inconvenience. The process of harmfulness has characteristics that make it special ; harmfulness prior statement is necessary; The onset of action is discretionary decision of the public administration; the defendant is the beneficiary of a favorable contested measure . The law should establish limits on the process of harmfulness , ours does not, but it is clear that the declaration of injury must be given within a period and the beginning of the contentious administrative action in another court . Like any judicial process, detrimental action generally ends by court order. Our legislation , as already stated , the detrimental action has not been treated , so in this research work expose concepts , legal analysis and proposals for improving our legal system